2018
DOI: 10.3892/ol.2018.8805
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of malignant and benign breast masses using automatic segmentation and features extracted from dynamic contrast‑enhanced and diffusion‑weighted MRI

Abstract: Magnetic resonance imaging exhibits high sensitivity but low specificity for breast cancer. The present study aimed to investigate whether combining morphology, texture features and kinetic features with diffusion-weighted imaging using quantitative analysis improves the accuracy of discriminating malignant from benign breast masses. In total, 104 and 171 malignant lesions in 205 women were included. Additionally, 13 texture and 11 morphology features were computed from each lesion using a semi-automated segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Other than DCE‐MRI, MR sequences such as nonenhanced T 1 ‐weighted images, diffusion‐weighted images, and T 2 ‐weighted images have been used to improve lesion characterization. Investigators have also developed multiparametric models combining diffusion‐weighted imaging with DCE‐MR for lesion discrimination, with accuracies up to 0.93. Specific features that were significantly different between benign and malignant lesions included entropy and signal enhancement ratio .…”
Section: Lesion Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Other than DCE‐MRI, MR sequences such as nonenhanced T 1 ‐weighted images, diffusion‐weighted images, and T 2 ‐weighted images have been used to improve lesion characterization. Investigators have also developed multiparametric models combining diffusion‐weighted imaging with DCE‐MR for lesion discrimination, with accuracies up to 0.93. Specific features that were significantly different between benign and malignant lesions included entropy and signal enhancement ratio .…”
Section: Lesion Classificationmentioning
confidence: 99%
“…Specific features that were significantly different between benign and malignant lesions included entropy and signal enhancement ratio . Jiang et al found that adding additional parameters to a multiparametric model improved accuracy of discrimination between benign and malignant lesions. For example, adding kinetic features to a model using shape and texture features from DCE‐MR improved accuracy, and adding an ADC threshold to this model improved accuracy again.…”
Section: Lesion Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics allowed the association of image traits with phenotypes, tissue characteristics, genomic signatures and protein expression patterns of a tumor [26][27][28][29][30]. To date, analysis of breast MRI textural features has been applied for the discrimination between malignant and benign lesions [31][32][33][34][35], correlation with tumor histological and molecular subtypes [36][37][38][39][40] and even prediction of chemotherapy response [41].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion‐weighted imaging has also been found to significantly improve lesion characterization . The addition of diffusion‐weighted imaging to multiparametric deep‐learning models has already been shown to improve accuracy of lesion characterization …”
mentioning
confidence: 99%